Load Reduction of Semi-Submersible Floating Wind Turbines by Integrating Heaving-Type Wave Energy Converters with Bang-Bang Control - Chen, Zheng; Yu, Jiarui; Sun, Jili; Tan, Ming; Yang, Shujie; Ying, You; Qian, Peng; Zhang, Dahai; Si, Yulin (Frontiers in Energy Research, 2022)
Floating offshore wind turbines (FOWTs) are subject to intensive structural loads due to the extra degrees of freedom (DOF) of the floating platform, which may shorten the fatigue lifetime of critical wind turbine structures. Integrating wave energy converters (WECs) into FOWTs could potentially help improve both overall energy capture and platform dynamic responses, thus is expected to reduce the levelized cost of energy (LCOE). In this work, a novel hybrid wind-wave energy platform consisting of a semi-submersible FOWT and three heaving-type WECs is proposed, and the feasibility of reducing FOWT dynamic responses and fatigue loads by integrating heaving-type WECs with different PTO control schemes is investigated. More specifically, the aero-hydro-servo-elastic-mooring coupled numerical model is established, and a preliminary study is performed to evaluate the dynamic responses and power production of the hybrid platform under various environmental conditions. Particularly, two kinds of PTO control strategies have been comparatively studied, which have shown that the active bang-bang control could effectively suppress the platform heave and pitch motion by up to 34.6 % and 17.1 %, respectively. Moreover, the tower-base fatigue damage equivalent load (DEL) has been reduced by up to 11.21 %, and the system power production could be increased by almost 6 %. Therefore, it is shown that integrating heaving-type wave energy converters with bang-bang control is able to effectively reduce the dynamic responses and fatigue loads of semi-submersible FOWT, while absorbing additional wave energy at the same time.